Marketing of Public Library Services in Balochistan: Planning and Prospects. - Abdul Baqi; Rasheed Ahmed (Journal of Quranic and Social Studies, 2022)
Abstract The purpose of this paper was to examine the marketing of library services in public libraries of Balochistan, and to identify the factors related to the use of different library marketing strategies in public libraries. Being quantitative in nature the study adopted survey method using close ended questionnaires for data collection from librarian and other related staffs in public libraries of Balohistan. The findings of the study depict that the librarians in public libraries have a positive perception towards the applying marketing strategies. It also identified factors relating to the marketing services and resources that are linked to the creation of awareness among librarian, lack of fund, poor internet quality, and not using library website and new trends of library marketing for libraray services. This study highlights the key factors related to the adaptation of libraray marketing services in libraries and provides outreach services to the readers. Library administrators by using these results can develop the library marketing plans to effectively promote their library services and resources.